2004
DOI: 10.1086/420867
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Structural Adjustment Due to Tidal Heating of Short‐Period Inflated Giant Planets

Abstract: Several short-period Jupiter-mass planets have been discovered around nearby solar-type stars. During the circularization of their orbits, the dissipation of tidal disturbance by their host stars heats the interior and inflates the sizes of these planets. Based on a series of internal structure calculations for giant planets, we examine the physical processes that determine their luminosity-radius relation. In the gaseous envelope of these planets, efficient convection enforces a nearly adiabatic stratificatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 37 publications
1
53
1
Order By: Relevance
“…In the past, the semimajor axis had been assumed to be constant when conducting tidal evolution studies (e.g., Bodenheimer et al 2001Bodenheimer et al , 2003Gu et al 2004). Jackson et al (2008b) calculate the evolutionary histories of the tidal dissipation rate for several EGPs, and find that in most cases the tidal heating rate increases as a planet moves inward and then decreases as the orbit circularizes.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In the past, the semimajor axis had been assumed to be constant when conducting tidal evolution studies (e.g., Bodenheimer et al 2001Bodenheimer et al , 2003Gu et al 2004). Jackson et al (2008b) calculate the evolutionary histories of the tidal dissipation rate for several EGPs, and find that in most cases the tidal heating rate increases as a planet moves inward and then decreases as the orbit circularizes.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In the proximity of its host star, this extra energy source may cause a planet to inflate beyond its Hill's radius and lose mass (Gu et al 2004). …”
Section: Planetary Inflation and Mass Lossmentioning
confidence: 99%
“…First, in order for the Roche lobe overflow to provide angular momentum, the actual shape of the Roche lobe should be taken into account. However, for computational simplicity, we adopt in this paper a spherically symmetric approximation (refer to Gu et al 2003, hereafter GBL03, for a detailed study). Second, we have only considered the contribution of ohmic dissipation P to the planetary inflation.…”
Section: Mass-loss Ratementioning
confidence: 99%
“…One is described in Zahn (1989, indicated with [Z]), the other in Goodman & Oh (1997, indicated with [G&O]). Ray et al 1987;Podsiadlowski 1996;Gu et al 2004;Ivanov & Papaloizou 2004), but none of these studies is directly applicable to our situation. Specifically for PSR B1718−19, Verbunt (1994) showed that the tidal energy is on the order of the potential energy of the star, assuming a ini a c or e ini ∼ 1 (here and below, the labels "ini" and "c" refer to those situations where the pulsar binary has just been formed and where the orbit has been circularised, respectively).…”
Section: Position Inmentioning
confidence: 88%